2018
DOI: 10.1088/1748-9326/aaeaa2
|View full text |Cite
|
Sign up to set email alerts
|

Global cost estimates of forest climate mitigation with albedo: a new integrative policy approach

Abstract: Climate change mitigation policies have usually considered forest-based actions as cheap and fast options to reduce CO 2 concentration in the atmosphere and slow down global warming. Most economic analyses, however, have ignored the effects of these actions on land surface albedo and the resulting effect on energy balance and temperature. This study estimates the marginal cost of forest mitigation associated with both carbon sequestration and albedo change, by introducing regional and forest-specific albedo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…The climate effects of forest‐based bioenergy can be augmented or diminished by associated changes in biophysical properties of land, such as surface albedo, emissions of biogenic volatile organic compounds, surface roughness, evapotranspiration and sensible heat fluxes that directly or indirectly affect climate (e.g. Anderson et al, 2011; Bonan, 2008; Favero et al, 2018; Lutz & Howarth, 2015; Luyssaert et al, 2018). These effects are complex and highly dependent on location, tree species and management practice, and have implications for global as well as regional and local climate (e.g.…”
Section: Non‐co2 Climate Forcersmentioning
confidence: 99%
“…The climate effects of forest‐based bioenergy can be augmented or diminished by associated changes in biophysical properties of land, such as surface albedo, emissions of biogenic volatile organic compounds, surface roughness, evapotranspiration and sensible heat fluxes that directly or indirectly affect climate (e.g. Anderson et al, 2011; Bonan, 2008; Favero et al, 2018; Lutz & Howarth, 2015; Luyssaert et al, 2018). These effects are complex and highly dependent on location, tree species and management practice, and have implications for global as well as regional and local climate (e.g.…”
Section: Non‐co2 Climate Forcersmentioning
confidence: 99%
“…To exclude the surface albedo in the assessments of land-based mitigation can result in the implementation of policies that are suboptimal or even counterproductive [4,5]. Indeed, recent research has consistently demonstrated the need to value the surface albedo alongside carbon in order to maximize mitigation benefits, particularly for forestry projects [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth paper in the focus collection, Favero et al (2018) conduct an economic analysis of the role of forests to mitigate climate change, and suggested albedo effects could be added to the analysis along with carbon sequestration. However, other research shows albedo effects on radiative forcing at the scale of actual land use change are minor and too weak to cause observable changes in temperature (Lee et al 2011).…”
Section: Carbon Accountingmentioning
confidence: 99%